PREFERENCES OF WINE CONSUMERS ON SERBIAN MARKET - Vlahović, Branislav; Potrebić, Velibor; Jeločnik, Marko (Economics of Agriculture, 2012)
Wine, as worldwide known beverage left deep traces in tradition of many nations, and way it is consumed, very often reflects culture, customs and lifestyles of local communities. Beside health benefits, wine is very often symbol and sign of prestige, especially within wealthy consumers, and its consumption is influenced mostly by tradition, confession, habits and level of life standard. General recognition of wine initiated poll research survey during 2011 with basic goal to perceive factors that determine demand and consumption of wine in Republic of Serbia. In other words, survey tried to establish what are the preferences, motives, and consumer attitudes when buying a wine in domestic market. Gained results could represent useful database to wineries and wine importers who can based on that estimate current market potential and their products niche in domestic market.